Impact of Pillars of Social Media Marketing on the Promotion of Business - S.Vasantha, Dr; NavithaSulthana, A (International Journal of Engineering and Technology, 2018)
Purpose: Social media marketing is the new phenomena in doing advent business online. Social media marketing has transformed earlier business strategy into digital business. This paper focus on how the uses of social media marketing lead to the promotion of business. With rapid growth of online shopper, the growth of business has increased and consumer change their traditional purchase intention into digitalization. The study focuses on how the use of internet technology and pillars associated with it leads to new era of businessgrowth. The main aim of the research is how the social media is the one of the channel to promote the business in the digital era. The growth of mobile usage and internet access among Millennials increases the E commerce.Design/methodology/approach: Based on literature review the impact of social media on the promotion of business is examined and conceptual model is developed to examine the relationship between study variablesPractical Implication: This research would be useful to the organization to understand what are the key areas to be concentrated to promote business through social media pillarsFindings: The depth literature survey shows that YouTube Face book followed by WhatsApp is most common surfed social media in India. The social media marketing facilitates E-brand loyalty, transparency of business, CRM and build stronger relationships with key stakeholders, which promotes business.Â